An Integrated, Size-Structured Stock Assessment of Antarctic Krill, Euphausia superba - Rui Wang (Frontiers Media S.A., 2021)
The Antarctic krill (Euphausia superba) fishery is the largest fishery in the Southern Ocean, and it has been operating for over 45 years. In the past decade, the spatial distribution of the krill fishery has focused on the Bransfield Strait off the Antarctic Peninsula (subarea 48.1). However, the high fishing effort and climate change have placed great pressure on krill resources in this region, and conservation concerns have been raised. Because aging krill is difficult and uncertain, we developed an integrated size-structured model to estimate the fishing mortality, recruitment and spawning biomass of krill. The results indicated that in 1992–2011, the average spawning biomass of krill ranged from 1.14 × 106 to 1.45 × 106 tons, the estimated biomass of the maximum sustainable yield (BMSY) ranged from 3.96 × 105 to 4.90 × 105 tons and the estimated average recruitment ranged from 2.3 × 1012 to 5.03 × 1012 individuals in the research area. We explored the effect of different data weighting schemes for the length data on the assessment output. However, our estimates also have uncertainties. In addition, an attempt was made to analyze the correlation between model-estimated recruitment and mature biomass with climate change. Future stock assessments of krill resources should be comprehensive and multimethod, and the management of krill resources should be based on science that considers the demand of fishing communities and ecosystem protection.